The benchmarking techniques in human resource management: A case study in business organization - Mohd Harif, Mohd Amy Azhar; Chee, Hee Hoe; Zainal Abidin, Suriati (World Business Institute, Australia, 2012)
Human Resource Management (HRM) is designing management systems in order to ensure that human talent is used effectively and efficiently to accomplish organizational goals.Hence, to ensure that the basic alignment of HRM parallel with overall organization strategy, there is a need to study the effectiveness of each HRM practices implied in the organization. In this respect, benchmarking study is identified to be one of the most effective tools to indicate the effectiveness of HRM practices in the organization.With this in view, this case study was conducted to digest and diagnose the HRM practices implied by the benchmarking community in the Northern Region of Malaysia.With the hope of understanding in depth of HRM practices, it will also indicate the strength and weaknesses each of the practices by identifying the gaps between importance and achievement and provide rooms for improvement.National Productivity Corporation Malaysia (NPC) has implemented this study in collaboration with Federation of Malaysian Manufacturers Northern Branch (FMM).Hence, this case study will use the secondary data for the purpose of analyzing.The study has used a comprehensive approach of benchmarking techniques, which assist the participating benchmarking community in establishing benchmarks, measure their own practices and identify best practices in key areas of HRM.A total of 6 companies participated the benchmarking study which comprised of a manufacturer of corrugated cartoons, a automation and robotics equipment manufacturer, manufacturer of agricultural chemicals, frozen seafood producer, meter cluster for automotive and automation equipment manufacturer and a conveyor system manufacturer.